2019
DOI: 10.1039/c9md00323a
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin inhibition and anti-cancer activities of ethyl 2-benzimidazole-5-carboxylate derivatives

Abstract: Sirtuin inhibitor potently inhibits the proliferation of H103 cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Among the cell lines evaluated, H103 showed a high sensitivity for BZD9Q1 and induced a prominent G2/M cell cycle arrest and apoptosis in these cells (Yeong et al, 2019). SIRT3 overexpression has been reported in HSC-3, UM-SCC-1, and UM-SCC-17B OSCC cell lines.…”
Section: Sirt3 In Oral Cancermentioning
confidence: 91%
See 2 more Smart Citations
“…Among the cell lines evaluated, H103 showed a high sensitivity for BZD9Q1 and induced a prominent G2/M cell cycle arrest and apoptosis in these cells (Yeong et al, 2019). SIRT3 overexpression has been reported in HSC-3, UM-SCC-1, and UM-SCC-17B OSCC cell lines.…”
Section: Sirt3 In Oral Cancermentioning
confidence: 91%
“…Till date, not even a single study reported the role of SIRT2 in oral cancer. Upregulation of SIRT3 has been observed in several OSCC cell lines and in OSCC tissue samples (Alhazzazi et al., 2011; Yeong et al., 2019). Till date, in the context of oral cancer, only a few studies have reported the role of SIRT1 and 3, and therefore, the results of such studies are not conclusive.…”
Section: Sirtuins: Types Location and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study ( Suk et al, 2019 ), a benzimidazole derivative carrying a pyrrolidine side chain ( 282) significantly suppressed sorafenib-resistant cell lines growth in xenograft model by inhibiting the phosphorylation of AKT, p70S6 and the downstream molecule RPS6, has unlocked another milestone in the treatment of hepatocellular carcinoma. Yeong et al ( Yeong et al, 2019 ) synthesized several new benzimidazole derivatives 283–287 and screened them against sirtuin cancer lines (SIRT1, SIRT2, and SIRT3). Among them, compound 284 elicited significant inhibition of SIRT1-3 compared to tenovin-6 (IC 50 (mean ± SD, µM): 7.7 ± 1.4 vs. 42.10, 5.6 ± 1.3 vs. 25.6, and 9.8 ± 2.0 vs. 82.65).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Over the years, benzimidazole and its derivatives have been extensively studied in the pharmaceutical field for a wide range of pharmacological activities, which are useful for drug development. Some of the pharmacological activities which have been reported include anti‐cancer, analgesic, anti‐histamine, anti‐inflammatory, anti‐acetylcholinesterase, anti‐fungal, anti‐tubercular, anti‐viral, anti‐malarial and anti‐protozoal [1–12] . Some benzimidazole‐based drugs which have been marketed are as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%